Alternatif Back Feeding Dengan Instalasi Kabel 20 kV Pada Auxiliary Transformer Analisis Biaya (Menggunakan Etap) - Afrianda, Rio (KILAT, 2024)
In order to actualize the 35,000 MW government program, the JAWA 2 Combined Cycle Power Plant (PLTGU) is built, with a power capacity of 800 MW and distributed trough a 500 kV interconnection system located in the PLTGU Tanjung Priok area, North Jakarta. This project have several stage before the operation such as planning, construction and testing/commissioning. In testing period, the electricity required for testing the equipment is supplied from the existing power grid or also known as back feeding. One of the alternatives for back feeding PLTGU Jawa 2 is to use electricity from the 20 kV GIS 150 kV cubicle of Priok Timur Lama, this method has the potential of delays if the installation of the 20 kV cable connection that supplies the auxiliary transformer unit is not carried out properly. The 20 kV cable connected to the auxiliary transformer bushing unit will experience cable stress if the bending radius of the cable in connecting the 20 kV cable to the auxiliary transformer bushing unit is not taken into account. From these constraints a study can be carried out on the installation design of the 20 kV cable connection that supplies the auxiliary transformer unit. moreover, a study to determine of the type of 20 kV cable is also necessary so that the power source can be optimally distributed to the equipment to be tested. With this study, the back feeding can proceed according to a predetermined schedule and any issue during the back feeding test can be anticipated beforehand.